Author Correction: Structural determinants and functional consequences of protein affinity for membrane rafts - Joseph H. Lorent (Nature Portfolio, 2018)
In the originally published version of this Article, financial support was not fully acknowledged. The PDF and HTML versions of the Article have now been corrected to include support from National Institute of General Medical Sciences, National Institutes of Health grant R01GM124072.